PEMANFAATAN TIK-TOK SEBAGAI MEDIA DAKWAH: Studi kasus Ustadzah Oki Setiana Dewi di akun @okisetaianadewi_official: Studi kasus Ustadzah Oki Setiana Dewi di akun @okisetaianadewi_official - Rahmadhani, Anis; Lailla Wikandina, Demanda (LPPM IAI Hasanuddin Pare-Kediri, 2023)
This article discusses the use of the Tik-Tok social media platform as a da'wah tool by a famous ustadzah, ustadzah Oki Setiana Dewi, through the official account @okisetianadewi_official. This case study aims to reveal how a religious figure uses the Tik-Tok platform in an effort to spread religious messages to a wide audience, especially the younger generation. The method used in this research is a qualitative descriptive method with data sources in the form of documents, video posts from social media accounts with analytical methods connecting with theories related to preaching, preaching messages, and also new media. The research results show that Ustadzah Oki Setiana Dewi has succeeded in utilizing TikTok as an effective medium for preaching, by creating content that is relevant, informative and inspiring. The TikTok account @okisetianadewi_official has become a popular channel for understanding the teachings of the Islamic religion and supporting moral values in a modern context. With this appearance, Ustadzah Oki Setiana Dewi conveys a da'wah message that remains based on the Al-Qur'an and Hadith with the da'wah content revolving around Islamic teachings in it, related to aqidah, sharia, and morals/muamalah with the aim of being easily accepted by the generation of Tik-Tok users. as a da'wah partner.